Alteraciones tiroideas mediante la realización de pruebas tiroideas y la relación con antecedentes familiares en mujeres que asisten a la consulta externa del Hospital Julius Doephner de la ciudad de Zamora - Vega Álvarez, Silvana Rocío (2016)
Thyroid hormones are essential for normal development of the individual, play an important role in the growth and formation of vitamins, as well as oxygenation and protein production. The aim of this study is to determine thyroid tests (TSH, T3 and T4) and the relationship with a family history in women attending at Julius Doephner hospital of Zamora city. The study was descriptive cross-sectional. He was made a total of 72 people who attended the Laboratory of Hospital Julius Doepfner city of Zamora, where the samples by venipuncture to which we applied the technique Elisa (Colorimetric Method) to obtain values were obtained TSH, T3 and T4. To fulfill one of the objectives of this study of family history information of the participants through the application of a survey and analysis of the samples was obtained. With the results we proceded to a statistical analysis, noting that of the 72 patients in the study, 2.8% had altered T3 values, 25.0% with values outside the normal range for T4, and 27.8% with values altered TSH, being a total of 40 people with these values. The data collected from surveys, indicate that 65.3% knew the disease, 79.2% reported not having a family history and 86.1% did not know the cause of the disease, not having any relationship between the results of these with tests thyroid.